Parallel Process in Supervision:: A qualitative investigation - Hewitt Taylor, Joanna; Rodway, Rosalind; Poole, Stella; Tyson, Rob (European Journal for Qualitative Research in Psychotherapy, 2006)
This study explored the phenomenon of parallel process as experienced by a group of four Gestalt and integrative counsellors and psychotherapists and four supervisors. It considered their direct experience of the phenomenon, their understanding and the meaning they ascribe to it, their ways of working with parallel process and consideration of any possible function.